CUSTOMER RELATIONSHIP MARKETING APPLICATION IN THE COAL INDUSTRY ON SHIP AGENCY SERVICES - Lilik Santoso; Lilik Setiawan; Muhammad Riza Firdaus (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
The study aims to analyze customer relationship marketing and customer loyalty through customer trust and customer satisfaction. The samples were selected using purposive sampling technique, based on which 100 respondents were selected. The data were analyzed using Partial Least Square. The hypothesis testing results show that customer relationship marketing has a significant positive effect on customer trust. Customer relationship marketing has a significant positive effect on customer satisfaction. Customer relationship marketing has a significant positive effect on customer loyalty. Customer trust has a significant positive effect on customer satisfaction. Customer trust has a significant positive effect on customer loyalty. Customer satisfaction has a significant positive effect on customer loyalty The mediation test results found that customer trust and customer satisfaction were able to mediate the effect of customer relationship marketing on customer loyalty, the higher customer trust and customer satisfaction, the higher effect of customer relationship marketing on customer loyalty.